1987
DOI: 10.1073/pnas.84.17.6117
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Z-RNA.

Abstract: Specific immunochemical probes for Z-RNA were generated and characterized to search for possible Z-RNA-like double helices in cells. Z-RNA was detected in the cytoplasm of fixed protozoan cells by immunofluorescence microscopy using these anti-Z-RNA IgGs. In contrast, autoimmune or experimentally elicited anti-DNA antibodies, specifically reactive with B-DNA or Z-DNA, stained the nuclei. Preor nonimmune IgGs did not bind to the cells. RNase A or T1 digestion eliminated anti-Z-RNA IgG binding to cytoplasmic det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…Alternatively, it is possible that double-stranded vRNA or DI segments may undergo an A-Z transition upon interaction with DAI. Notably, Z-RNA has previously been detected in the cytoplasm and nucleolus of eukaryotic cells (Zarling et al, 1987), and circular dichroism studies have shown that the Zα domain facilitates the transition from A-RNA to Z-RNA under near-physiological conditions (Brown et al, 2000), indicating that dsRNAs in the left-handed Z conformation can serve as physiological substrates for DAI, and for other proteins with Zα domains.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that double-stranded vRNA or DI segments may undergo an A-Z transition upon interaction with DAI. Notably, Z-RNA has previously been detected in the cytoplasm and nucleolus of eukaryotic cells (Zarling et al, 1987), and circular dichroism studies have shown that the Zα domain facilitates the transition from A-RNA to Z-RNA under near-physiological conditions (Brown et al, 2000), indicating that dsRNAs in the left-handed Z conformation can serve as physiological substrates for DAI, and for other proteins with Zα domains.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions enhance the D3'-endo ribose pucker and the anti base conformation typical ofthe RNA A form (23). Thus it is more difficult for an RNA to assume the various polymorphic structures that have been observed for DNA, which is more flexible, although other RNA forms are possible (25). Thus our experiments demonstrating tDNA aminoacylation should not be surprising from a structural perspective, since the absence of the 2' OH in the tDNA must allow the flexibility and polymorphism necessary to achieve the typical RNA solution structure recognized by the appropriate aminoacyl-tRNA synthetase.…”
mentioning
confidence: 82%
“…It appears that this double helical structure could have Z-RNA-like properties analogous to those observed with Z-DNA (Hall et al 1984). A precedent for the existence of doublestranded cytoplasmic Z-RNA has been reported in protozoa (Zarling et al 1987). The lack of a major open reading frame and the strong potential for secondary structure formation lead to the speculation that the D17Sill testis transcript may serve a structural or regulatory, rather than informational, role during germ cell differentiation.…”
Section: Discussionmentioning
confidence: 89%